Non-Traditional Maritime Security Challenges and Regional Collaboration For Environmentally Sustainable Development In The Indian Ocean Region - Mishka Husen Balfas (Syntax Literate, 2021)
The Indian Ocean region is currently becoming the world's attention. Although many parties see good opportunities from various aspects, this region still has its own challenges. The Indian Ocean provides a complex geopolitical framework in which foreign powers and local state interests are deeply intermingled. This paper discusses how the collaboration and synergy undertaken by countries in the Indian Ocean region face non-traditional maritime security challenges, especially those directly related to ocean health and the environment. Moving on from the three SDG points directly related to environmental issues, countries in the Indian Ocean region have shown collaboration to maintain regional stability from all aspects, especially environmentally sustainable development. Furthermore, more intensive cooperation is needed because there are more and more challenges, especially non-traditional ones.